Biology and Control of Calomicrus apicalis Demaison, 1891 (Col.: Chrysomelidae), a New Pest of Cedrus libani A. Rich. in Turkey - Aytar,Fatih (2011)
Cedrus libani A. Rich., known as Lebanon Cedar or Taurus Cedar, is an important tree species native to the Taurus Mountains in Turkey. Worldwide, the largest forests of C. libani occur in southern Turkey and cover an area of 417.188,5 ha, although relict stands can also be found in the Emirdağ Mountains of Central Turkey and near the Akıncı and Çatalan villages of the Black Sea coast, in northern Turkey. Additionally, there are also relict forests in Syria (400 ha) and Lebanon (2,200 ha). Calomicrus apicalis Demaison, 1891 (Col.: Chrysomelidae) is an endemic species and a new pest of Taurus Cedar in Turkey. This insect was found for the first time in Hassa-Akbez forests (Hatay province) in 1891. The populations of C. apicalis have been increasing rapidly since 2000, and from an initial area of 20-30 ha this harmful leaf beetle spread rapidly and nowadays can be found on over 3000 ha of forest, not only in the Taurus Mountains but also in the new plantations/forests in Eastern and Central Anatolia. Beetle attacks have been threatening and affecting the health of young stands of C. libani, as they feed on needles of seedlings and young trees in the spring. The leaves affected by the pest undergo subsequent discoloration then dry up. In this paper we report on the most important aspects of the biology and distribution of this new pest in Turkey, and discuss possibilities of management and control against it.